(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Emotional labor has been defined as the effort required to display certain emotions as part of a job role. In the healthcare sector, emotional labor is an essential component of service provision as healthcare workers are required to display empathy, compassion, and understanding towards patients. The purpose of this paper is to examine the problems and prospects of adopting emotional labor strategies for the enhancement of patient satisfaction in hospitals.